Impact of Global Crude Oil Price Shocks on Iraq's National Budget (2004-2020): Dampak Fluktuasi Harga Minyak Mentah Global terhadap Anggaran Nasional Irak (2004-2020) - Diaa Hussein Saud; Ismael Hammadi Mejdel; Adnan Taha Qirfoa; Alyaa Hussin Khalaf (Academia Open, 2025)
General Background: Oil-exporting economies are highly vulnerable to fluctuations in global crude oil prices, with fiscal stability closely tied to external market dynamics. Specific Background: Iraq exemplifies this fragility due to its rentier structure, where over 90% of state revenues derive from oil exports, making the national budget especially sensitive to shocks. Knowledge Gap: While oil price volatility is widely studied, limited research has empirically examined the asymmetric transmission of these shocks through revenues, expenditures, and deficits within Iraq’s post-2003 fiscal framework. Aims: This study investigates the dynamic relationship between crude oil price shocks and Iraq’s national budget from 2004 to 2020, assessing both short- and long-term effects. Results: Using the ARDL approach with data from the World Bank, OPEC, and Iraq’s Ministry of Finance, findings reveal strong cointegration and unidirectional causality from oil prices to revenues and expenditures, alongside a destabilizing feedback loop between expenditures and deficits. Fiscal outcomes demonstrate procyclical spending, rapid adjustment rates, and heightened vulnerability during crises such as the 2008 financial downturn, the 2014–2015 oil shock, and the COVID-19 pandemic. Novelty: This is the first comprehensive econometric analysis linking Iraq’s fiscal performance to oil price volatility post-2003. Implications: Results underscore the urgent need for structural reforms, diversification policies, and international financial support to mitigate fiscal fragility in resource-dependent states.Highlight : The research analyzes Iraq’s budget sensitivity to global oil price fluctuations. Results confirm strong dependence of revenues and expenditures on oil income. The study suggests diversification policies to stabilize fiscal performance. Keywords : Oil Price Shocks, Fiscal Vulnerability, National Budget, Iraq, ARDL Model